Catalytic hydrolysis of sodium borohydride via nanostructured cobalt–boron catalysts. (5th January 2016) - Wang, Yan; Li, Tianle; Bai, Shuchong; Qi, Kezhen; Cao, Zhongqiu; Zhang, Ke; Wu, Shiwei; Wang, Dan
Abstract: In this study, nanostructured Co–B/Cu sheet catalysts were successfully fabricated using electroless plating method at ambient temperature. The results illustrated that the morphology, composition, structure and surface roughness of the catalysts were immensely dependent upon the concentration of BH4 − . The as-prepared catalyst with the average size of about 52.2 nm exhibited significantly enhanced catalytic activity during hydrolytic dehydrogenation of sodium borohydride. The hydrogen release rate was 7935.6 mL min −1  g −1 and the activation energy was 43.3 kJ mol −1 . This enhanced catalytic activity was attributed to the small particle size and the high surface roughness, which provided many defects (such as angle, step, or edge etc.), offering more active sites on the catalyst surface. Meanwhile, it was found that the excess amount of BH4 − used to synthesize the catalysts was not increasing the catalytic activity, when the reduction agent BH4 − concentration was over 0.8 g L −1 . Furthermore, the Co–B catalyst deposited 0.8 g L −1  BH4 − retained about 80% catalytic activity of its initial activity after 5 cycles, which indicated that the hydrogen release rate decreased gradually. The reason might be due to the damage of nanostructure and the decrease of Co species and boron species in concentration after 5 cycles. Graphical abstract: Highlights: Nanostructured Co–B/Cu sheet samples are synthesized by electroless plating method at ambient temperature. The Co–B catalysts exhibit high catalytic activity in the hydrolysis of NaBH4 . The nanostructure and surface roughness of Co–B catalysts are crucial for their high catalytic activity.